Seasonally variable interactions between dissolved organic matter and mineral particles in an agricultural river (data set) - Groeneveld, Marloes (Uppsala University, 2021)
Dataset containing 2 excel files:
- Fyris_EEMs contains all fluorescence excitation emission spectra (corrected)
- Fyris_data contains all other data

The dataset was originally published in DiVA and moved to SND in 2024.

Dataset containing 2 excel files:
- Fyris_EEMs contains all fluorescence excitation emission spectra (corrected)
- Fyris_data contains all other data

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Seasonally variable interactions between dissolved organic matter and mineral particles in an agricultural river (data set)
Keywords: geochemistry; geokemi; Geochemistry; Geokemi